Pollination Ecology of Rhynchosia Heynei Wight and Arn. (Leguminosae), An Endemic Medicinal Herbaceous Shrub Species of Peninsular India - Raju, A. J. Solomon; Ramana, K. Venkata (Journal of Institute of Science and Technology, 2018)
Rhynchosia heynei is an endemic shrub in dry deciduous forests of peninsular India. It is medicinally important and used locally for the treatment of different diseases. Despite its medicinal value and endemic status, no studies were made on the pollination ecology of this shrub to understand the factors leading to its endemic status. In this connection, the standard protocols were followed for the systematic study of the pollination in the Nallamalai forest of Eastern Ghats of Andhra Pradesh. The study indicated that the plant produces nectariferous bisexual flowers. The flowers were self-compatible and equipped with explosive pollination mechanism adapted for melittophily. The fruit set occurred through self and cross-pollination. Mature and dry pods dehisce explosively to disperse seeds. Regeneration occurred through perennial root stock and seeds during rainy season but the regeneration rate is poor due to rocky and dry habitat with little moisture and nutrient content. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 32-44